The adolescent spurt and sexual maturation in girls active and not active in sport - Geithner, C. A.; Woynarowska, B.; Malina, R. M. (Annals of Human Biology, 1998)
Girls actively training in sport (n=23) and girls not active in sport (n=26) were compared in terms of ages at peak height velocity (PHV) and menarche, the interval between ages at PHV and menarche, and ages at attaining stages of pubic hair and breast and the estimated duration of the stages. Subjects were longitudinally followed from about 11-18 years of age. Stature and weight were measured and stages of pubic hair and breast development were rated at approximately quarterly intervals between the initial observation and 14 years of age, at semiannual intervals until 16 years, and at irregular intervals subsequently. Age at menarche was obtained prospectively. The active girls trained 12 hours per week in rowing, track and swimming for an average of 3.9+/-1.2 years during puberty and the growth spurt. Longitudinal stature records for individual girls were fitted with kernel regression to estimate age at PHV (years). The interval between age at PHV and age at menarche was calculated. Ages at appearance of pubic hair and breast stages 3, 4 and 5 were calculated by back-interpolation, while intervals between stages 3 and 4 were calculated after log 10 transformation. Peak height velocity and menarche occur, on average, slightly later in girls active in sport, but the differences are not significant. The interval between PHV and menarche, PHV (cm/year), ages at attaining pubic hair and breast stages 3, 4 and 5, and estimated intervals between adjacent stages also do not significantly differ between girls actively training in sport and those not active in sport. Thus, regular training in sport during puberty and the adolescent spurt does not apparently influence the timing and progression of somatic and sexual maturation in girls.